Infrared Imaging of Photochromic Contrast in Thiazolothiazole-Embedded Polymer Films - Nuren Z. Shuchi; Tyler J. Adams; Naz F. Tumpa; Dustin Louisos; Glenn D. Boreman; Michael G. Walter; Tino Hofmann (Optics)
The increasing demand for optical technologies with dynamic spectral control has driven interest in chromogenic materials, particularly for applications in tunable infrared metasurfaces. Phase-change materials such as vanadium dioxide and germanium–antimony–tellurium, for instance, have been widely used in the infrared regime. However, their reliance on thermal and electrical tuning introduces challenges such as high power consumption, limited emissivity tuning, and slow modulation speeds. Photochromic materials may offer an alternative approach to dynamic infrared metasurfaces, potentially overcoming these limitations through rapid, light-induced changes in their optical properties. This manuscript explores the potential of thiazolothiazole-embedded polymers, known for their reversible photochromic transitions and strong infrared absorption changes, for use in tunable infrared metasurfaces. The material exhibits low absorption and a strong photochromic contrast in the spectral range from 1500 <semantics>cm−1</semantics> to 1700 <semantics>cm−1</semantics>, making it suitable for dynamic infrared light control. This manuscript reports on infrared imaging experiments demonstrating the photochromic contrast in thiazolothiazole-embedded polymer, and thereby provides compelling evidence for its potential applications in dynamic infrared metasurfaces.